International Student Education as the Cornerstone of Cultural Exchanges 深化国际教育内涵，夯实人文交流之基: The Case of Xi’an Jiaotong University 以西安交通大学国际教育为例 - Feng, Xiaojing; Wen, Guangrui; Ji, Ting; Sun, Xianghe; Zhao, Wei (Journal of International Students, 2020)
Amity between the people holds the key to sound state-to-state relations. Supporting people-to-people exchanges, international education is of great significance to the building and maintaining of a good relationship between countries. This paper analyzes the humanistic values of international education and proposes two characteristics of China’s international education, respectively named the bidirectional cultural exchanges and social benefits. Taking Xi’an Jiaotong University as an example, the paper illustrates how international student education helps to promote cultural and social exchanges between China and foreign countries, and paves the way for intercultural learning and understanding. 国之交在于民相亲。国际教育作为人文交流的重要途径和有效载体，对扩大民间友好具有重要意义。本文通过剖析国际教育的人文内涵，分析国际教育的双向文化传播属性、外溢属性的特点，以多种角度阐述国际教育对中外人文交流的促进。并以西安交通大学为例，以翔实的数据案例，阐明立足高校如何做好国际教育，以促进中外人文社会交流，铺就文明互鉴之路。